Small angle scattering from soft matter—application to complex mixed systems - Boué, François; Cousin, Fabrice; Gummel, Jérémie; Oberdisse, Julian; Carrot, Géraldine; El Harrak, Abdeslam (Comptes rendus. Physique, 2007)
The advantage of small angle neutron scattering associated with isotopic labelling through deuteration is illustrated in the case of mixed systems, created by associating already well-known systems of characteristic structures; this is also important for applications. Our first mixed system associates charged polymer chains, polyelectrolytes (here polystyrene sulfonate, PSS), with oppositely charged particles, proteins (here lysozyme). Different fractions of deuterated water (D 2O) mixed with normal water are used to match the scattering length density of the protein or of the polymer in non-deuterated or deuterated version. First, this allows us to separate the protein and the polymer signal: we can then distinguish a case where the structures of each species alone in water are hardly modified by mixing, except for interconnections yielding a gel, and a case inducing complete change into a structure common to both species, made of aggregated globules. Second, using, for counterions of the polyions, deuterated TetraMethylAmmonium, together with matching both protein and polymer, we establish unambiguously the counterion release into the solvent. Third, matching only a fraction of polymer chains, the other being deuterated, we extrapolate at zero deuterated fraction their form factor and describe the chain conformation inside the complexes. Fourth, we illustrate the possibilities of modelling the signal on a second example of mixed system: a nanocomposite made of silica particles surrounded by polymer dispersed into a deuterated polymer matrix. Chains are then visible in such reinforced polymer system, in particular when it is submitted to elongation: we discuss a possible model for an ideal system, introducing the scattering contribution from deformed chains, another subject studied at LLB. To cite this article: F. Boué et al., C. R. Physique 8 (2007). Les possibilités de marquage par deutériation associées à la diffusion de neutrons aux petits angles sont illustrées dans le cas des systèmes mixtes, créés par l'association de systèmes simples aux structures caractéristiques connues dans le domaine de la matière molle ; ces systèmes mixtes sont très importants dans les applications. Le premier système choisi résulte du mélange de chaînes polymères chargées en solution dans l'eau (polyélectrolytes), ici du polystyrène sulfonate, avec des protéines de charge opposée, ici du lysozyme. Des mélanges eau lourde/eau légère à différents taux sont utilisés pour adapter la densité de longueur de diffusion du solvant à celle de la protéine ou du polymère. Ceci nous permet d'abord de séparer les signaux des deux espèces ; dans un cas, la répartition spatiale des deux composants est à peine modifiée, à l'exception de connexions menant à un gel, dans un autre un changement complet mène à une structure, partagée par les deux espèces, d'agrégats globulaires. Deuxièmement, en utilisant comme contre-ions des polyions, le TetraMethylAmmonium deutéré, nous démontrons sans ambiguïté le relargage des contre-ions dans le solvant. Troisièmement, en éteignant en même temps les signaux des protéines et des chaînes non deutérées, en présence d'une fraction de chaînes deutérées, nous pouvons extrapoler à fraction nulle le signal d'une seule chaîne et son facteur de forme, et en déduire sa conformation au sein des complexes. Finalement, nous illustrons les possibilités de modélisation sur un deuxième système mixte, un nanocomposite de particules de silice entourées par des chaînes polymères introduites dans une matrice polymère deutérée. Les chaînes sont alors visibles dans un tel système polymère renforcé, en particulier quand il est soumis à une élongation. Nous discutons un modèle possible qui introduit la diffusion anisotrope des chaînes et la “perte d'affinité”, un autre sujet étudié au LLB. Pour citer cet article : F. Boué et al., C. R. Physique 8 (2007).